A proteomic analysis of the functional effects of fatty acids in NIH 3T3 fibroblasts - Magdalon, J.; Hatanaka, E.; Romanatto, T.; Rodrigues, H.; Kuwabara, W.; Scaife, C.; Newsholme, Philip; Curi, R. (Biomed Central, 2011)
Previous studies have demonstrated that long chain fatty acids influence fibroblast function at sub-lethal concentrations. This study is the first to assess the effects of oleic, linoleic or palmitic acids on protein expression of fibroblasts, as determined by standard proteomic techniques. The fatty acids were not cytotoxic at the concentration used in this work as assessed by membrane integrity, DNA fragmentation and the MTT assay but significantly increased cell proliferation. Subsequently, a proteomic analysis was performed using two dimensional difference gel electrophoresis (2D-DIGE) and MS based identification. Cells treated with 50 μM oleic, linoleic or palmitic acid for 24 h were associated with 24, 22, 16 spots differentially expressed, respectively. Among the identified proteins, α-enolase and far upstream element binding protein 1 (FBP-1) are of importance due to their function in fibroblast-associated diseases. However, modulation of α-enolase and FBP-1 expression by fatty acids was not validated by the Western blot technique.